Healthcare policy changes in an era of health workforce shortage - Yoel Angel; Gil Fire (BMC, 2023)
Abstract In their recent IJHPR article, Wimpfheimer and colleagues outline the implications for the field of anesthesia of two major healthcare policy changes in Israel: The Yatziv Reform in licensing foreign medical graduates and the efforts to reduce residents' on-call shift duration. We argue that these reforms are necessary to strengthen the healthcare workforce and improve the quality of care in the long term, even though they may limit the availability of healthcare personnel for several years, particularly in the field of anesthesia. In this commentary, we examine the background to these policy changes, their likely impact on the medical workforce in Israel in general, and propose steps to reconcile these reforms with the global and national shortage of physicians. We urge policymakers to allocate the required resources and begin preparing for an era of continuous mismatch between physician supply and demand, which will necessitate creative solutions, increased reliance on technology, and the introduction of paramedical professionals to help offload tasks and better utilize the scarce physician workforce.